Pengaruh Buku Cerita Terhadap Peningkatan Sikap Peduli Kebersihan Lingkungan Sekolah pada Anak Kelas V Sekolah Dasar di Kecamatan Gamping Kabupaten Sleman Propinsi Daerah Istimewa Yogyakarta - Yustiana Olfah; Ni Ketut Mendri; Bondan Palestin (Journal of Health (JoH), 2017)
Background: Elementary school education is the basic level education where students were forged with many kind of study subject where each subject has to be mastered by the students. On the other hand students were also educated with attitude and behavior values that will be the basis for further developments in the future. One of the important attitude and behavior that needs to be educated early is environmental hygiene concern. Story book is a proper medium for attitude and behavior educaton for children, since they can accommodate children reading capacity and interest. Story books are usually written with short sentence, also simpler vocabulary and grammar compared to adult reading which makes them very effective in affecting the soul of the children. Objectives: To reveal the influence of story book with hygiene environmental schools hygiene concern theme towards attitudes and behavior of hygiene environmental schools hygiene concern on students of elementary schools in the District Gamping, Sleman Special Region of Yogyakarta. Method : Quasi-experimental "Pre test Post test with Control Design" Research Design. The research sampling was purposive sampling. Story books with environmental hygiene concern theme was given by reading together with the respondents and the researchers then followed by an explanation, while the control group didn’t exposed with the story books. Pre test and post test were used to determine the attitudes and behavior of hygiene environmental school concern before and after given the story book. Hypothesis testing using SPSS for Windows with T-test method with a significance level of p <0.05. Results: The attitude analysis result of the experimental and control groups with Independent sample t-tests obtained sig. (2-tailed) of 0.000 <0.05, which means story book gives significant influence on student’s attitude related to environmental hygiene concern. While behavior analysis result of the experimental and control groups with independent sample t-test obtained sig. (2-tailed) of 0,343 > 0,05, which means story book gives no significant influence on student’s behavior related to environmental hygiene concern. Conclusion: There is a correlation of using storybooks with environmental school hygiene concern themes towards the environmental school hygiene concern attitude and while no observed correlation towards the environmental school hygiene concern behavior.